Passenger Car Tires and Wheels Development - Manufacturing - Application - Leister, Günter (Springer International Publishing, 2018)
Starting from the beginning, this book explains the development process of all parts related to the topics tire, wheel and tire pressure monitoring system. This is continued by the modern project management methods in the development process of the parts and the necessary tests to build up this safety relevant components. Modern methods for simulations are described. .